2023
DOI: 10.1021/acs.jctc.3c00077
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Behavior of SARS-Cov-2 Spike Protein Variants: Evolutionary Jumps in Sequence Reverberate in Structural Dynamic Differences

Abstract: SARS-CoV-2 has evolved rapidly in the first 3 years of pandemic diffusion. The initial evolution of the virus appeared to proceed through big jumps in sequence changes rather than through the stepwise accumulation of point mutations on already established variants. Here, we examine whether this nonlinear mutational process reverberates in variations of the conformational dynamics of the SARS-CoV-2 Spike protein (S-protein), the first point of contact between the virus and the human host. We run extensive micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 74 publications
(161 reference statements)
0
1
0
Order By: Relevance
“…They found that epitope exposure, measured by accessible surface area, was observed to remain constant or increase significantly during the transition from the ‘down’ to the ‘up’ state of RBD, impacting the binding of some but not all of the evaluated antibodies. Other studies used explicit dynamic information on wild-type SARS-CoV-2 S protein and several mutants to reveal the intrinsic determinants of epitope presentation and the mechanisms of antibody escape [ 153 , 154 , 155 ]; in all of these cases, mutations modify the glycan-shield of the S protein with a strong impact on its dynamics and recognition properties.…”
Section: Therapeutic Implications—targeting Conformational and Assemb...mentioning
confidence: 99%
“…They found that epitope exposure, measured by accessible surface area, was observed to remain constant or increase significantly during the transition from the ‘down’ to the ‘up’ state of RBD, impacting the binding of some but not all of the evaluated antibodies. Other studies used explicit dynamic information on wild-type SARS-CoV-2 S protein and several mutants to reveal the intrinsic determinants of epitope presentation and the mechanisms of antibody escape [ 153 , 154 , 155 ]; in all of these cases, mutations modify the glycan-shield of the S protein with a strong impact on its dynamics and recognition properties.…”
Section: Therapeutic Implications—targeting Conformational and Assemb...mentioning
confidence: 99%